INFLUENCE FACTORS ON EMPLOYEE PERFORMANCE AT PT. CIPTA SEJATI REVOLUTION - Artiyany, Megawhati (Jurnal Ekonomi Balance, 2018)
This research aims to determine the effect of recruitment on employee performance at PT. Cipta Sejati Revolution. The types of data used in this study are qualitative and quantitative data. The data sources used in this study are primary and secondary data. The population in this study is all employees at PT. Cipta Sejati Revolution with sampling techniques in this study using Saturated Sampling,which amounted to 41 respondents. The results obtained in this study are evidenced by the results of a simple regression analysis equation that is Y= 25.82+0.35X. The result of the correlation coefficient equation is 0.44. The result of the coefficient of determination is 0.1936 or 19.36%. After testing t obtained the results of the value of >  (3,066 > 1,685) then H0  rejected and received H1,  meaning there is a significant influence between recruitment on the performance of employees at PT. Cipta Sejati Revolution.